Analisis Genetik Sifat Ketahanan Melon (Cucumis melo L.) terhadap Virus Kuning - Hermawan, Entit; ,, Sobir; Efendi, Darda (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACTResistance to yellow virus (YV) is an important breeding trait in melon. However information regarding genetic inheritance pattern of the character are limited. This study aimed to provide information on genetic control for resistance to YV in melon caused by Tomato Yellow Leaf Curl Virus (TYLCV). Twenty genotypes from three major melon groups (dudaim, cantaloupe, and inodorous) were evaluated using controlled inoculation method. The results revealed that one line, MEV1 from the dudaim group, showed high resistance to YV; while other lines belong to cantaloupe and indororus indicated as highly susceptible lines. Screening of the F1 from crossing between resistant and susceptible parents resulted in resistant F1 after inoculation and planted in endemic location. Subsequently, evaluation on F2 population revealed a non-normal distribution for disease severity score, indicating that resistance to YV in melon was controlled by major genes. Chi-square (χ2) test resulted in 13:3 ratio and indicated that the resistance to YV was controlled by 2 genes pair with dominant and epistasis recessive actions.Keywords: dominant and epstasis recessive action, major gene, Bemicia tabaci, Begomovirus